Atresia of the Left Oviduct and Abnormality of the Caecum of a 12-month-old Layer:A Case Report - Sulaiman , M.H.; Saidu, L.; Abdu, P.A. (International Journal of Poultry Science, 2010)
This report describe a rare case of congenital defects involving the atresia of the left oviduct with the accompanying abnormalities of ovaries and caecum observed in a 12-month-old layer presented to the Avian Ambulatory Clinic of the Veterinary Teaching Hospital, Ahmadu Bello University, Zaria. At post mortem, a thin wall oviduct measuring 18 cm long, which opens into the cloaca, was noticed, while the left oviduct was completely absent. In addition the right hypolastic oviduct had a large cyst, with a morphometric measurement of 18 cm by 14 cm by 7 cm and containing 1.25 litres of clear non proteinous fluid, weighing 1.01 kg. When the cystic fluid was cultured in blood agar, at 37oC for 72 h, no bacteria colony growth was observed. However biochemical analysis revealed a composition of electrolytes. The bird also had undeveloped ovaries, malformed illeocaecal junction cranially measuring 6.5 cm. To our knowledge, this is the first case report of congenital abnormalities of the atresia of the left oviduct, malformed caecum and hypoplastic right oviduct in ISA-Brown layer bird in Nigeria.